Collaborative Governance Dalam Penanganan Abrasi Pantai Berbasis Ekonomi Biru Di Pulau Bengkalis - Rusadi, Sylvina; Setiawan, Rizky (Universitas Djuanda, 2025)
Indonesia is a country that has thousands of islands stretching from west to east. This causes the wealth of marine resources owned by the State of Indonesia. Unfortunately, many islands in Indonesia have experienced environmental damage due to abrasion. Abrasion has a destructive impact on the coastal environment where people live. The impacts felt are not only from an ecological perspective but also impact the economy and socio-culture of the surrounding community. This study aims to analyze and describe the implementation of collaborative governance based on the dynamics of collaboration, collaborative actions, and the impact of adaptation on the collaboration process in handling coastal abrasion on Bengkalis Island. The method used in this study is a qualitative method with a descriptive type, meaning that the research conducted describes the entirety of the phenomena found and involves several people as informants. The data sources used in this method are observation, interviews, and research documentation. This study found that collaborative governance in handling abrasion still has various dynamics between collaborators, which makes the handling process slow.